Influence of habitat complexity on fish density and species richness in structurally simple forereef seagrass meadows - Ho, Nina Ann Jin; Ooi, Jillian Lean Sim; Affendi, Yang Amri; Chong, Ving Ching (De Gruyter, 2018)
Seagrass meadows are highly productive habitats that support commercially and ecologically important fishes and invertebrates. However, evidence of fish-habitat relationships are seldom drawn from forereef seagrass meadows that are structurally simple in terms of species richness and relative size and, consequently, their role as habitats is unclear. In this study, fish-habitat relationships were examined in such meadows in the forereef seagrasses of Tinggi Island and Babi Besar Island, Malaysia, by documenting habitat complexity attributes (canopy height, shoot density and percent cover), distance to adjacent coral reefs, and water depth within 2×2 m quadrats. Fish assemblages were recorded using the Remote Underwater Video Station method. A total of 1166 individuals from 86 taxa were found and enumerated. This study showed that (1) fish density and species richness were significantly associated with seagrass percent cover alone; (2) commercially important carnivores formed the majority of the fish populations in the meadows, and (3) fish density and species richness were positively correlated with distance to the nearest adjacent coral reef, indicating the need to account for the effects of neighboring habitats in studies of this nature. Thus, structurally simple seagrass meadows are still important fish habitats, especially as feeding grounds for commercially significant carnivores.